Pengaruh Metode Eksperimen Terhadap Hasil Belajar Fisika Kelas VIII SMP Negeri 2 Tondano - Yoktan Mangar; Patricia Mardiana Silangen; Jimmy Lolowang (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
Experimental activities are inseparable in learning physics at school. The purpose of this study was to determine the effect of the experimental method on physics learning outcomes for class VIII students of SMP Negeri 2 Tondano. The method used in this study is an experimental method by presenting treatment to two classes with the same level of ability through the form of learning methods. From the results of the analysis of the data normality test using test statistics on the SPSS program